Socio-economic Linkages of the Ife-Ijesa Frontier Population in Southwestern Nigeria - Aloba, Oluwole (Obafemi Awolowo University, 2014)
This study has developed a methodology for determining the socio-economic linkages of frontier population. This is achieved by a study of the historical and current socio-economic linkages of the communities in the Ife-Ijesa frontier area of southwestern Nigeria.